Electrochemical Genotyping of Single‐Nucleotide Polymorphisms by using Monobase‐Conjugated Modified Nanoparticles. Issue 4 (12th February 2014) - Mehdi khoshfetrat, Seyyed; Mehrgardi, Masoud A.
Abstract Currently, construction of DNA biosensors for single‐nucleotide polymorphisms (SNPs) genotyping is challenging, particularly in terms of speed and cost. We demonstrate a single platform for genotyping the SNPs by using electrochemical signals of modified nanoparticles (MNPs). To this end, silver and gold nanoparticles (AgNPs and AuNPs) are modified by using cysteine and cysteamine hydrochloride as linkers, respectively. The monobases are subsequently attached to the MNPs through their 5' phosphate group, forming a phosphoramidate bond with free amino groups of the linkers. Electrooxidation signals of AgNPs and/or 3, 4‐diaminobenzoic acid (DABA) are monitored as analytical signals for SNP genotyping. In the presence of DNA polymerase I (Klenow fragment), the coupling of monobase‐conjugated MNPs (MMNPs) is induced to the mutant sites of duplex DNA, following the Watson–Crick base‐pairing rule, which leads to a substantial change in the signal intensity of MMNPs. The method is able to distinguish complementary targets with a linear dynamic range of 20–1000 pM and 50–1500 pM of mutant DNA, with reliable reproducibility [relative standard deviation (RSD)=5.1 % and stability (RSD=4.2 %). In this study, an accurate, sensitive, fast, and cost‐effective approach for SNP genotyping is introduced.